Barrier refractory materials for aluminum electrolyzers based on concentrated Kampanovskii kaolin; Refractories and Industrial Ceramics; Vol. 47, N 6 - Vakalova T. V. Tatyana Viktorovna; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Egorova E. Yu.; Reshetova A. A.; Kamnev S. V.; Dikarev D. A.; Romanenko N. G. (2006, 2006)
The authors describe the results of developing compositions and technologies for barrier materials based on the products of concentration of kaolins from the Kampanovskii deposit for cathode lining in aluminum electrolyzes. High-density dry barrier mixtures with different Al2O-SiO2 ratios (from 0.42 to 0.76) have been obtained, which can be used in two-layer linings for aluminum electrolyzers (in the high-alumina and silica layers). The composition and properties of these mixtures correspond to known foreign analogs